(3GdbhI GdedReI ddYbO GdEOGQi (B/ s - (3CMeO eMeO gRGY GdTeQi s; (3KQhJ HOhi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JfGhdfG ef NdGd gPG GdHMK GdeJhGVY HMK GdJRGe WQai GdQGHWI GdYbOjI HGdYbO GdEOGQi heGgjI GdJRGeGJ GdJi JbY Ydi YGJb GdEOGQI hefgG GdJRGegG HGMJQGe ebJVjGJ MSf GdfjI ai JfajP GdYbO hGdYed Ydi JfajPg hGMJQGe cGaI TQhWg hGMJQGe GdeOO GdebQQI ddJfajP (B. (3ceG JfGhdfG GjVG TQhW JWHjb cd ef fXQjI Yed GdCejQ hfXQjI GdXQha GdWGQFI hGKQgeG Ydi GdJRGeGJ GdGOGQI GdeJYGbOI hMbhb GdeJYGbO eYgG ceG HjfG eOi GdJRGe GdeJYGbO eY GdGOGQI HGdYbO GdGOGQi hPdc ai Xd cd ef GdXQha GdYGOjI hGdXQha GdGSJKfGFjI hGKQ acQI GdGYJHGQ GdTNUi ai JfajP GdGdJRGeGJ GdJi fU YdjgG GdYbO hGMcGe GdJYGbO ef GdHGWf hGKQ ehGabI LgI GdEOGQI Ke HjfG GjVG fXQjI GdUYhHGJ GdeGOjI ZjQ GdeJhbYI hGKQgG Ydi JfajP GdYbO GdEOGQis
Through this modest thesis, we dealt with discussing the commitment of the contracting parties with the administrative contract and what are the obligations that are incumbent on the department. Among them are the obligation to respect the requirement of good will in performing the contract, endeavoring to performing and respecting all of its conditions and the terms assigned for implementation. We also dealt with the conditions of applying the theory of the Prince's action and the theory of the emergent circumstances and their effect of the obligations of the contracting department and the rights of the contractor with it. We also explained the extent of the contractor's commitment with the department with the administrative contract. This is within each of the normal and exceptional circumstances; besides the effect of the personal esteem idea in performing the obligations stated in contract, the provisions of sub-contracting and the effect of the department's approval. We also explained the theory of the unpredictable materialistic difficulties and their effect on performing the administrative contract
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B110-112s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3GdbhI GdedReIs; (3GdYbO GdEOGQi s; (3fXQjI GdUYhHGJ GdeGOjI ZjQ GdeJhbYI s; (3GdXQha GdWGQFIs; (3GdJYGbO ef GdHGWf s; (3GdXQha GdYGOjI s; (3ehba GdbVGA GdeUQj s; (3GdJReGJ GdeJYGbO eY GdEOGQI s; (3GdXQha GdGSJKfGFjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes